Lymphadenectomy in the Treatment of Colon Cancer: A Survival Nalysis - Corrêa, Romualdo Silva; Oliveira Lima, Luciana Ayres de; Macedo, Isa Maryana Araújo Bezerra de; Rêgo, Amália Cinhtia Meneses; Araújo-Filho, Irami (International Journal of Innovative Research in Medical Science, 2019)
Colon cancer is a curable disease when restricted to the bowel and colectomy, the primary treatment. However, the presence and number of resected lymph nodes influence the therapeutic approach and prognosis of the patient. To evaluate the impact of the number of resected lymph nodes on the overall survival of patients treated for colon cancer at the League of Cancer Hospital - Natal - State of Rio Grande do Norte (RN) - Northeast Brazil. A retrospective observational study of 80 patients with colon cancer from Dr. Luiz Antônio Hospital (Natal-RN / Brazil), considering the period 2007-2014. Data were collected through medical records review. Survival rates were calculated and compared using the non-parametric Kaplan-Meier and Wilcoxon tests, respectively. All patients underwent radical surgical treatment associated or not with chemotherapy and/or radiotherapy treatment. The median survival time for the group of patients who had 12 or more resected lymph nodes was 9.4 years, in contrast to the 3.3 years of those who had less than 12 lymph nodes. Conclusion: It was concluded that a total of 12 or more resected lymph nodes confirmed by histopathology is associated with increased long-term survival in patients with colon cancer undergoing radical colectomy with or without chemotherapy and radiotherapy.